SUMBER DAYA DALAM IMPLEMENTASI KEBIJAKAN KEPARIWISATAAN DI OBJEK WISATA BUDAYA RUMAH BETANG ENSAID PANJANG KABUPATEN SINTANG - E.01110009, Nurhalimah (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
The purpose of this writing is to investigate and analyze the resources in the implementation of tourism policies in cultural attractions Rumah Betang Ensaid Panjang.This type of research is exploratory qualitative approach.The problems that exist in this exciting attraction for investigational remember there are still some things that cause a lack of effectiveness of the policy and less impact on the development of cultural attractions Rumah Betang Ensaid Panjang. The factors that cause a lack of effective tourism policy at the Rumah Betang Ensaid Panjang that resource conditions. Human resources are lacking in quality and capital resources are still lacking in attraction led to the development of Rumah Betangis the bottleneck. In addition, the size and purpose of the policy is too broad, the characteristics of the implementing agencies that have not been prominent, less attitude/tendency ( dispositon ) of the implementers and the lack of communication between organizations and implementing good activity also affect development in Rumah Betang Ensaid Panjang. Environmental factors such as geographical conditions as well as economic, social, political and cultural tourism policies also lead to less effective. In addition there are other factors such as the commitment of the region, the availability of infrastructure, private sector involvement, public awareness has also led to a lack of effective tourism policy at the cultural attractions Rumah Betang Ensaid Panjang. Of the various factors mentioned above, the culture and expectations of future Department of Tourism Sintang district can make strategic policies to develop the attraction Rumah Betang Ensaid Panjang.Keywords: Policy, Implementation, Tourism, Rumah Betang .